The Influence of Self-Efficacy, Work Stress, and Work Environment on Employee Performance - Miki Mardela; Rina Dwiarti (LifeSciFi, 2026)
In an increasingly competitive business environment, improving employee performance has become a crucial concern for organizations. This study aims to analyze the influence of self-efficacy, Work stress, and work environment on employee performance. The research employed a quantitative approach with a saturated sampling technique, involving all 33 employees as respondents. Data were collected using questionnaires and analyzed through validity and reliability tests, multiple linear regression, t-test, F-test, and the coefficient of determination. The results show that self-efficacy has a positive and significant effect on employee performance. In contrast, job stress and work environment have no significant effect. However, simultaneously, the three variables significantly influence employee performance. The adjusted R square value of 0.234 indicates that self-efficacy, job stress, and work environment collectively explain 23.4% of employee performance, while the remaining 76.6% is influenced by other factors outside this study. These findings emphasize that employees’ confidence in their abilities is the dominant factor in enhancing performance, whereas job stress and work environment do not show direct significant effects in this organizational context.